PENGARUH HARGA, CITA RASA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG KONSUMEN MIXUE ICE CREAM - Lydia Permadha Rukmar Lydia; Arie Firmansyah (JEBS (Journal of Economic and Business Student), 2023)
The purpose of this study is to test and evaluate the effect of price, taste, and product service quality on the repurchase intention of Mixue Ice Cream customers who are located at Bojong Sereh Bandung. This study involved a sample of 30 participants who were Mixue consumers. The research was conducted by collecting primary data through the use of questionnaires. The data analysis approach used in this study involves the use of multiple linear regression through the use of SPSS (Statistical Product and Service Solution). The test findings indicate that the price, taste, and service quality variables positively influence the repurchase intention of Mixue Ice Cream consumers.